Hurricane María and Public Health in Puerto Rico: Lessons Learned to Increase Resiliency and Prepare for Future Disasters - Gabriela R. Guerra Velázquez (Ubiquity Press, 2022)
Background: On September 20, 2017, Hurricane Maria, a devastating Category 5 storm struck the Caribbean Island of Puerto Rico and officially took the lives of 2 975 people although the Harvard University survey in 2018 placed that number much higher at 4 645 [1, 2]. The island's infrastructure was devastated. Eight months later in May 2020, many vital services including telecommunications, utilities, and health care systems had not yet been repaired. Objectives: To (1) review the immediate public health problems and the longer-term repercussions of Hurricane Maria; (2) identify pre-existing infrastructural deficiencies, health disparities, and problems in governance that may have increased vulnerability and delayed recovery; and (3) offer proposals for preventive measures to increase resiliency and adequately prepare Puerto Rico for future disasters. Methods: Data from the CDC and the Puerto Rico's Health Department were collected and analyzed. Government publications, news articles, scholarly journal entries and previous research were examined. Interviews were conducted with local citizens and public health professionals. The author's personal experience is referenced. Findings: The Puerto Rican Electric Power Authority (PREPA) and the Puerto Rico Aqueduct and Sewer Authority (PRASA) both had severely weakened infrastructures before the hurricane as a result of a massive financial crisis that had begun in 2006. These pre-existing weaknesses increased vulnerability and made reconstruction more challenging. Approximately 95% of the cell towers in Puerto Rico sustained significant damage during the hurricane and resulted in almost total loss of cell phone communication [3]. Subpar management of relief efforts by both federal agencies and the local government further hindered recovery, resulting in mass emigration of Puerto Ricans. The public health problems of Hurricane Maria continue to plague Puerto Rico's citizens and will have long-term consequences. Conclusion: Lack of resilience in Puerto Rico's infrastructure and government agencies rendered the island highly vulnerable to the detrimental effects of Hurricane María. Improvements to infrastructures and a transition towards a more sustainable way of life could improve Puerto Rico's preparation and response to future disasters - natural and human-made.